Limitations on the role of frequency in L2 acquisition [dataset] - Stutterheim, Christiane von; Lambert, Monique; Gerwien, Johannes (Universität, 2020)
This data set contains files associated with a study on motion event encoding in three L1 (French, German, English) and two L2 (German, English) gr...
Gesehen am 06.07.2020
Keywords: Forschungsdaten; Datenbank